Association between sociodemographic characteristics and exposure types in patients with Hepatitis C - Tiroli, Carla Fernanda (2021)
Objectives was to analyze the association bewteen sociodemographic characteristics and exposure types. This is an analytical cross-sectional study and quantitative, based on secondary data from the Viral Hepatitis forms notified by the municipalities of the 17th Health Regional of Paraná from 2015 to 2018. The data were analyzed in the Software Statistical Package for the Social Science for Windows. In the bivariate and multivariable analysis, the prevalence ratios and their respective 95% confidence intervals were calculated by using Poisson regression with robust adjustment of variance, and a 0,05-significance level. In the multivariable analysis, a statistically significant association was found between the male gender variable and the following exposure types: injectable drugs, inhalant drugs or crack, injectable medicine and three or more sexual partners. Conversely, there was an association between the age group from 18 to 59 years and the following exposure types: inhalant drugs or crack, tattoo and piercing, dental treatment and three or more sexual partners. In the group with low level of education, it was noticed an association between schooling and exposure types, with less prevalence, of the following factors: transfusion and dental treatment. Finally, using inhalant drugs or crack and having three or more partners were exposure factors to HCV associated with male gender and the age group of 18 to 59 years. Using drugs and injectable medicine were exposure factors associated with males, while tattoo and piercing and dental treatment were associated with the age group up to 59 years.